The dualistic role of Lyn tyrosine kinase in immune cell signaling: implications for systemic lupus erythematosus - L’Estrange-Stranieri, Elan; Gottschalk, Timothy A.; Wright, Mark D.; Hibbs, Margaret L. (Frontiers in Immunology, 2024)
Systemic lupus erythematosus (SLE, lupus) is a debilitating, multisystem autoimmune disease that can affect any organ in the body. The disease is characterized by circulating autoantibodies that accumulate in organs and tissues, which triggers an inflammatory response that can cause permanent damage leading to significant morbidity and mortality. Lyn, a member of the Src family of non-receptor protein tyrosine kinases, is highly implicated in SLE as remarkably both mice lacking Lyn or expressing a gain-of-function mutation in Lyn develop spontaneous lupus-like disease due to altered signaling in B lymphocytes and myeloid cells, suggesting its expression or activation state plays a critical role in maintaining tolerance. The past 30 years of research has begun to elucidate the role of Lyn in a duplicitous signaling network of activating and inhibitory immunoreceptors and related targets, including interactions with the interferon regulatory factor family in the toll-like receptor pathway. Gain-of-function mutations in Lyn have now been identified in human cases and like mouse models, cause severe systemic autoinflammation. Studies of Lyn in SLE patients have presented mixed findings, which may reflect the heterogeneity of disease processes in SLE, with impairment or enhancement in Lyn function affecting subsets of SLE patients that may be a means of stratification. In this review, we present an overview of the phosphorylation and protein-binding targets of Lyn in B lymphocytes and myeloid cells, highlighting the structural domains of the protein that are involved in its function, and provide an update on studies of Lyn in SLE patients.